Sedimentary and diagenetic controls on reservoir quality of low-porosity and low-permeability sandstone reservoirs in Chang101, upper triassic Yanchang Formation in the Shanbei area, Ordos Basin, China. (July 2019) - Chen, Junfei; Yao, Jingli; Mao, ZhiGuo; Li, Qi; Luo, Anxiang; Deng, Xiuqin; Shao, Xiaozhou
Abstract: There are many reservoirs with low porosity and low permeability in the world, and many large oilfields have been found in these reservoirs. Unlike conventional reservoirs, the genesis of low-porosity and low-permeability reservoirs and the controls of relatively high-porosity and high-permeability zones are still unclear. This study takes the Chang101 reservoir sandstones of the Shanbei area in the Ordos Basin, China, a typical low-porosity and low-permeability, as an example. Chang101 sandstones are fine-grained to medium-grained, moderately to well sorted arkose and lithic arkose deposited in a delta plain environment. It is a typical low porosity and low permeability reservoir with an average porosity of 10.21% and an average permeability of 2.88 mD. Pore types mainly include primary intergranular pores and secondary dissolved pores. The main controls on the reservoirs are the sedimentary environment and diagenesis. The sedimentary environment determines the initial properties of the reservoir sandstones, including the material composition and texture that determine the primary porosity and permeability. Diagenesis further transforms the reservoir quality to develop heterogeneity in the porosity and permeability. The reservoir sandstones have undergone complex diagenetic processes and are currently in stage A of mesodiagenesis. Compaction accounts for the major reduction of the primary porosity of the sandstones. Different types of cementation have both positive and negative influences on reservoir quality. Carbonate cementation, quartz overgrowths and some authigenic clay cementation(i.e., I/S and illite) are major pore-filling components, that reduce the reservoir quality. An appropriate amount of chlorite resists compaction and prevents quartz overgrowth, but excessive chlorite coatings fill the pores and block the pore throats. The laumontite cement is not only resistant to compaction but also easily dissolved to form a large number of effective secondary pores. The dissolution of feldspar and rock fragments plays a role in contributing to connecting the isolated intergranular pores and increasing the secondary pores. Relatively high porosity and high permeability zones are deposited in high-energy environment, mainly delta plain distributary channel sandstones with more detrital quartz, fewer rock fragments and coarser grains than other sandstones, were deposited in high-energy environment. There is weaker compaction and less or no carbonate cement, with the preservation of the primary pores by chlorite coatings and an increase in the pores by the dissolution of laumontite cement. Highlights: Basic characteristics of the Chang 101 reservoir were analyzed. Types and genesis of diagenesis were detailed exposited. Sedimentary environment control the innate inheritance of the reservoir. Diagenesis transforms the quality of reservoirs seriously. A general mode of relationship between sedimentology and diagenesis were proposed.